Temporal Trends in the Incidence of Human Immunodeficiency Virus Infection and Risk Behavior among Injection Drug Users in Baltimore, Maryland, 1988-1998 - Kenrad E. Nelson; Noya Galai; Mahboobeh Safaeian; Steffanie A. Strathdee; David D. Celentano; David Vlahov (2002)
Although the incidence of and mortality from acquired immunodeficiency syndrome have declined recently in the United States, data are needed on the incidence of human immunodeficiency virus (HIV) and risk behaviors among injection drug users (IDUs). The authors studied the temporal trends of HIV incidence and risk behavior, ascertained through semiannual confidential interviews, between 1988 and 1998 in a cohort of 1,532 HIV-seronegative IDUs in Baltimore, Maryland. An additional 338 HIV-negative drug users were recruited in 1994 and were studied by using the same methods. Overall, 277 persons seroconverted to HIV during 8,826.45 person-years of follow-up, an incidence of 3.14 per 100 person-years. The incidence per 100 person-years declined over time from 4.45 in 1988–1990 to 3.35 in 1991–1994 to 1.84 in 1995–1998, a decline of 12% per year. HIV infections were associated with injection of cocaine, more frequent injection, needle sharing, and injection in a shooting galley. Sexual behavior variables associated with HIV incidence included a sexually transmitted infection, male homosexual behavior, and sex with another IDU. These data suggest that high-risk behavior and HIV incidence among IDUs have decreased recently in Baltimore. Nevertheless, additional prevention strategies are needed in these populations.